2022
DOI: 10.3390/cancers14143379
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Hyposalivation and Xerostomia in Childhood Cancer Survivors Following Different Treatment Modalities—A Dutch Childhood Cancer Survivor Study Late Effects 2 Clinical Study (DCCSS LATER 2)

Abstract: Background: Limited data are available on the risk factors of salivary gland dysfunction in long-term childhood cancer survivors (CCS). The objective of this cross-sectional study, part of the multidisciplinary multicenter Dutch CCS Study Late Effects 2 (DCCSS LATER 2), was to assess the prevalence of and risk factors for hyposalivation and xerostomia in CCS. Methods: From February 2016 until March 2020, 292 CCS were included. Data with regard to gender, age at study, diagnosis, age at diagnosis, and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 43 publications
(90 reference statements)
0
19
1
Order By: Relevance
“…For the detection of dry mouth, we saw a similar trend. In 4.0% of CCS, dentists reported that complaints of xerostomia were present [ 6 ], while 9.4% of CCS experienced xerostomia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the detection of dry mouth, we saw a similar trend. In 4.0% of CCS, dentists reported that complaints of xerostomia were present [ 6 ], while 9.4% of CCS experienced xerostomia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SALI subproject selected CCS who had received head and neck radiotherapy (H&N RT) or total body irradiation (TBI), and CCS who had not. The inclusion procedure for the SALI subproject has previously been described in detail [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, other studies failed to demonstrate any adverse effect of CT on salivary glands in the early stage of cancer treatment [18][19][20]. Long-term data are scarce [21,22], and most of them focused on hematopoietic stem cell transplantation (HSCT) recipients [23,24]. Reduced salivary flow has been observed even 5 to 15 years after CT [21,22].…”
Section: Introductionmentioning
confidence: 99%